TRANSFORMATIONS OF MERCURY, IRON, AND SULFUR DURING THE REDUCTIVE DISSOLUTION OF IRON OXYHYDROXIDE BY SULFIDE - Slowey A.J.; Brown G.E. (My University, 2007)
Methylmercury can accumulate in fish to concentrations unhealthy for humans and other predatory mammals. Most sources of mercury (Hg) emit inorganic species to the environment. Therefore, ecological harm occurs when inorganic Hg is converted to methylmercury. Sulfate- and iron-reducing bacteria (SRB and FeRB) methylate Hg, but the effects of processes involving oxidized and reduced forms of sulfur and iron on the reactivity of Hg, including the propensity of inorganic Hg to be methylated, are poorly understood. Under abiotic conditions, using a laboratory flow reactor, bisulfide (HS-) was added at 40 to 250 μM h-1 to 5 g L-1 goethite (α-FeOOH) suspensions to which Hg(II) was adsorbed (30-100 nmol m-2) at pH 7.5. Dissolved Hg initially decreased from 103 or 104 nM (depending on initial conditions) to 10-1 nM, during which the concentration of Hg(II) adsorbed to goethite decreased by 80% and metacinnabar (β-HgS(s)) formed, based on identification using Hg LIII-edge extended X-ray absorption fine structure (EXAFS) spectroscopic analysis. The apparent coordination of oxygens surrounding Hg(II), measured with EXAFS spectroscopy, increased during one flow experiment, suggesting desorption of monodentate-bound Hg(II) while bidentate-bound Hg(II) persisted on the goethite surface. Further sulfidation increased dissolved Hg concentrations by one to two orders of magnitude (0.5 to 10 nM or 30 nM), suggesting that byproducts of bisulfide oxidation and Fe(III) reduction, primarily polysulfide and potentially Fe(II), enhanced the dissolution of β-HgS(s) and/or desorption of Hg(II). Rapid accumulation of Fe(II) in the solid phase (up to 40 μmol g-1) coincided with faster elevation of dissolved Hg concentrations. Fe(II) served as a proxy for elemental sulfur [S(0)], as S(0) was the dominant bisulfide oxidation product coupled to Fe(III) reduction, based on sulfur K-edge X-ray absorption near edge structure (XANES) spectroscopy. In one experiment, dissolved Hg concentrations tracked those of all sulfide species [S(-II)]. These results suggest that S(-II) reacted with S(0) to form polysulfide, which then caused the dissolution of β-HgS(s). A secondary Fe-bearing phase resembling poorly formed green rust was observed in sulfidized solids with scanning electron microscopy, although there was no clear evidence that either surface-bound or mineralized Fe(II) strongly affected Hg speciation. Examination of interrelated processes involving S(-II) and Fe(III) revealed new modes of Hg solubilization previously not considered in Hg reactivity models. © 2006 Elsevier Inc. All rights reserved.